Plan de Marketing para la empresa Fumicar S.A. del cantón Pasaje, provincia del Oro. - Noboa Rivera, Erick Daniel (2025)
The general objective of this research was to develop a marketing plan for the company “Fumicar S.A.”, in order to increase the efficiency in the offer of its services and improve its position in the market. A research with a qualitative and quantitative approach was used, using the descriptive and analytical methods, which allowed to investigate the characteristics that affect the services offered by the company, then the development of a proposal with advertising strategies through digital tools was carried out. The information supporting the work was obtained through an interview with the manager and a survey of 362 clients. For the analysis of the information, the Google Forms platform was used, where it was found that 75% of the clients corresponded to direct banana export companies and 25% to independent clients. The results were tabulated using frequency tables and graphs, which allowed identifying that 12.50 % of respondents consider advertising in the company's service offerings to be regular. Subsequently, a PESTEL situational diagnosis and the 7 Ps were carried out, providing key information for the execution of the ANSOFF and SWOT matrices; in conclusion, the proposal proposed focuses on marketing strategies and tactics based on digital marketing, in order to improve the positioning of Fumicar in the market and customer loyalty.